Comparison of self-expandable and balloon-expanding stents for hybrid ductal stenting in hypoplastic left heart complex. (30th August 2016) - Goreczny, Sebastian; Qureshi, Shakeel A.; Rosenthal, Eric; Krasemann, Thomas; Nassar, Mohamed S.; Anderson, David R.; Morgan, Gareth J.
Abstract: Objectives: We aimed to compare the procedural and mid-term performance of a specifically designed self-expanding stent with balloon-expandable stents in patients undergoing hybrid palliation for hypoplastic left heart syndrome and its variants. Background: The lack of specifically designed stents has led to off-label use of coronary, biliary, or peripheral stents in the neonatal ductus arteriosus. Recently, a self-expanding stent, specifically designed for use in hypoplastic left heart syndrome, has become available. Methods: We carried out a retrospective cohort comparison of 69 neonates who underwent hybrid ductal stenting with balloon-expandable and self-expanding stents from December, 2005 to July, 2014. Results: In total, 43 balloon-expandable stents were implanted in 41 neonates and more recently 47 self-expanding stents in 28 neonates. In the balloon-expandable stents group, stent-related complications occurred in nine patients (22%), compared with one patient in the self-expanding stent group (4%). During follow-up, percutaneous re-intervention related to the ductal stent was performed in five patients (17%) in the balloon-expandable stent group and seven patients (28%) in self-expanding stents group. Conclusions: Hybrid ductal stenting with self-expanding stents produced favourable results when compared with the results obtained with balloon-expandable stents. Immediate additional interventions and follow-up re-interventions were similar in both groups with complications more common in those with balloon-expandable stents.